2017
DOI: 10.1108/ijwbr-12-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

How can family winegrowing businesses be sustained across generations?

Abstract: We investigate how family winegrowing businesses can be sustained across generations. Design/methodology/approach We engaged a multi-level case study approach. Twenty-seven semi-structured interviews were conducted with three winegrowing firms in New Zealand. All family members (both senior and next generation) employed in each business were interviewed alongside non-family employees. Findings Three key dimensions-knowledge sharing, entrepreneurial characteristics, and leadership attributes-were identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…As for Zikmund, Babin, Carr, & Griffin (2010), they referred a case study as a description of a particular person, group, organization, or event that face a situation in business context. Hence, the case study is used to generate theory (Woodfield, Shepherd, & Woods, 2017) In addition, this study employed a multiple case analysis which enables the researcher to explore differences within and between cases to replicate findings across cases (Yin, 2014;Bizri, 2016;Woodfiel et al, 2017). Since comparisons are to be drawn, it is imperative that the cases are chosen carefully so that the researcher can predict similar results across cases, or predict contrasting results based on a theory (Yin, 2014;Boyd, Royer, Pei, & Zhang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As for Zikmund, Babin, Carr, & Griffin (2010), they referred a case study as a description of a particular person, group, organization, or event that face a situation in business context. Hence, the case study is used to generate theory (Woodfield, Shepherd, & Woods, 2017) In addition, this study employed a multiple case analysis which enables the researcher to explore differences within and between cases to replicate findings across cases (Yin, 2014;Bizri, 2016;Woodfiel et al, 2017). Since comparisons are to be drawn, it is imperative that the cases are chosen carefully so that the researcher can predict similar results across cases, or predict contrasting results based on a theory (Yin, 2014;Boyd, Royer, Pei, & Zhang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In a third study Woodfield, Shepherd, and Woods (2016) investigated three family winegrowing businesses to understand the impact of key dynamic capabilities on business succession. Woodfield et al, (2016) noted that individuals growing up and working at family businesses accumulated strong tacit knowledge and business acumen not easily replicated by non-family members. Similarly, Chirico and Nordqvist (2010) research found dynamic capabilities were evident.…”
Section: Dynamic Capabilities and The Wine Sectormentioning
confidence: 99%
“…Researchers in previous works started to inquire how the younger and older generation engage in knowledge creation and sharing since knowledge has been often "perceived as a kind of the company's 'anchor '" (Hadryś-Nowak, 2018), creating a competitive advantage and subsequently positively affecting intergenerational sustainability across generations (e.g. Chirico, 2008;Nordqvist and Chirico, 2010;Muskat and Zehrer, 2017;Woodfield, Shepherd, and Woods, 2017). Family business scholars claim that the CEMJ 109…”
Section: Purpose and Motivationmentioning
confidence: 99%